The fiscal multiplier: positive or negative? - Juha Tervala (Aboa Centre for Economics (ACE), 2009)
This study examines whether the fiscal multiplier can be negative for certain types of government spending. The key result is that the fiscal multiplier can be negative if there is a high degree of substitutability between private and government consumption and government consumption is complementary to leisure.
Keywords: E62; H31; H42; 330; fiscal policy; fiscal multiplier; effectiveness of fiscal policy